2016
DOI: 10.3892/ol.2016.4095
|View full text |Cite
|
Sign up to set email alerts
|

ERβ overexpression results in endocrine therapy resistance and poor prognosis in postmenopausal ERα-positive breast cancer patients

Abstract: Abstract. The aim of the present study was to investigate the role of estrogen receptor (ER) β in the prognosis of ERα-positive breast cancer in postmenopausal women, and its effect on the efficacy of endocrine therapy. Tissue specimens from 195 patients with postmenopausal breast cancer were analyzed. ERβ expression levels were detected using immunohistochemical staining. Kaplan-Meier analysis was performed to assess patient survival, and the difference in survival was analyzed using the log-rank test. Cox re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…However, in another study including 78 women who were postmenopausal with primary stage II to III invasive breast cancer, ERβ did not change when comparing samples from before and after endocrine treatment [45]. Since the role of ERβ in breast cancer remains unclear, the latest studies have made efforts to explore the relationship between ERβ and clinical outcome in many aspects, including the predictive value of ERβ expression [46], the ERβ to ERα ratio [45] and the DNA promoter hypermethylation of ERβ [47], especially in patients who have undergone endocrine therapy [48,49] and chemotherapy [44,50]. In general, numerous studies have verified that ERβ is an independent prognostic and/or predictive factor in breast cancer, although the conclusion is still controversial.…”
Section: Prognostic Value Of Erβ In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, in another study including 78 women who were postmenopausal with primary stage II to III invasive breast cancer, ERβ did not change when comparing samples from before and after endocrine treatment [45]. Since the role of ERβ in breast cancer remains unclear, the latest studies have made efforts to explore the relationship between ERβ and clinical outcome in many aspects, including the predictive value of ERβ expression [46], the ERβ to ERα ratio [45] and the DNA promoter hypermethylation of ERβ [47], especially in patients who have undergone endocrine therapy [48,49] and chemotherapy [44,50]. In general, numerous studies have verified that ERβ is an independent prognostic and/or predictive factor in breast cancer, although the conclusion is still controversial.…”
Section: Prognostic Value Of Erβ In Breast Cancermentioning
confidence: 99%
“…For example, Guo et al showed that compared to patients with low ERβ expression, patients with high ERβ expression in breast cancer tissue displayed a significantly lower median tumor-free survival time [ 48 ]. Another study of 195 postmenopausal females with stage I or II ERα-positive breast cancer who underwent endocrine therapy showed that ERβ overexpression results in reduced disease-free survival (DFS) and poor prognosis [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen affects the breast cancer primarily by its expression in tumor tissues. ERα was shown to promote cell proliferation and angiogenesis [34], while ERβ could lead to a poor prognosis of breast cancer by increasing endocrine therapy resistance [35]. In addition, progesterone plays a key role in the regulation of important reproductive functions and can exert its effects through both nuclear PRs and membrane PRs [36].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, high ERβ2 protein expression in ERα-positive BCa and reduced PR expression was correlated with poor response to TAM [ 39 ]. Higher ERβ1 protein expression level was associated with reduced DFS, and correlated with poor prognosis in TAM-treated ERα-positive BCa in post-menopausal women [ 40 ] and reduced DFS with endocrine therapy [ 41 ] and poor progression-free survival in patients with TNBC [ 42 ]. High levels of ERβ2 cytoplasmic expression alone or combined nuclear stains predicted worse OS [ 43 ].…”
Section: Erβ Isoform Expression and Bca Subtypesmentioning
confidence: 99%